Technical and economic aspects of the production of chips during the cultivation of willow white (Salix alba) - Butsko, Andrei A.; Pashynski, Vasil A.; Rodzkin, Aleh I. (Journal of the Belarusian State University. Ecology, 2018)
The article presents the results of the technical and economic assessment of the production of woodchips in the adaptive cultivation of tree and shrub species with a short growth period – the Clone Wolmianka willow white (Salix alba). The total cost of production of wood chips is 6,57–7,64 Belarusian rubles / us.m3. With a planned profitability of 0 %, the simple payback period of the required investments will be 12–15 years, the manufacturer’s selling price will be 7,89–9,17 Belarusian rubles / us. m3, the average annual net profit of 105,0–108,3 BYR / ha, Internal rate of return 23,5–24,0 %, return on investment 796,9–822,2 %. Taking into account the variation of the planned profitability from 9,1 to 115,1 %, the simple payback period of the required investments varies from 3 to 9 years, the manufacturer’s selling price will be 8,48–17,97 Belarusian rubles / us. m3, the average annual net profit 157,99–709,1 bel. rub./ha, the internal rate of return is 30,6–82,0 %, the return on investment is 1196,3–5383,3 %. With a discount rate of 17–21 %, the net present value of capital investment varies from 286 to 509 Belarusian rubles / ha, which corresponds to the option (revenues +10 %, costs –10 %). For the option (incomes +5 %, costs –5 %), the net present value varies from 78 to 242 BYR / ha. In the basic version, as well as variants (incomes –5 %, expenses  +5 %) and (income –10 %, expenses +10 %), the net present value of capital investments assumes negative values.
Keywords: Fast-growing tree and shrub species; willow; Salix alba; clone Volmyanka; technological map; cost structure; production cost; return on investment; average annual net profit; internal rate of return; net present value; payback period